Solar PV Refrigeration in Saharan Environement - Mouloud Tizzaoui; Hamou Soualmi; Achor Mansouri (university Of Eloued جامعة الوادي, 2020)
The Adrar is the largest city in Algeria; predominantly an agricultural province with more than 70% of the population is living in rural areas living on agriculture. Some perishable vegetables like tomato account for about 25-30% losses, besides deterioration in quality. The climate of Adrar province, each year spreads over an important hot and dry period. Nevertheless, the storage of these products currently relies on refrigeration processes to vapor compression, a huge consumer of electrical energy. Considering that the demand for cooling increases with the intensity of solar radiation, this document presents the potential of the city of Adar in southern Algeria to integrate the concept of sustainable development in the agricultural sector as the main alternative for transforming solar energy in cold. The case study of a storage capacity of around 3 tons of tomatoes gave an approach to calculating the GPV generator at around 27 kWh / day of electricity power. This technology considered as a promising concept for investment in the south of Algeria. This will ensure self-sustained, environment-friendly, economic development Saharan zone
Intervention
Keywords: Thermal load; Cold Room; Solar Photovoltaic; Electrical Power and Sahara Environment